The VANET-Solution Approach for Data Packet Forwarding Improvement - Hammood, Omar A.; M. N. M., Kahar; Mohammed, Muamer N.; Hammood, Waleed A.; Junaida, Sulaiman (American Scientific Publisher, 2018)
Vehicular Ad-hoc Networks (VANETs) are ad hoc wireless mobile networks which is important role in commercial applications and safety of public vehicular communications. In VANETs, data routing is a major problem because of its quick change in topology and vehicular high mobility. The routing protocols that base on vehicular position are attracting much interest because of the availability and advancement of devices equipped with GPS. A major problem with VANETs is the frequent disruptions in the path of vehicles due to the high mobility of the participating vehicles. This can lead to the breaking of established links and result in low throughput, delay in service delivery, less overhead as well as low rate of delivery. In this paper, the Civil Defiance Vehicle (CDV) approach is proposed. The proposed approach (CDV-VANET) compared to VANET, incorporates a potential score-based strategy which is traditionally better in performance and might achieve less delay in service delivery with a higher rate of delivery.